Performance of atmospheric plasma sprayed HA coatings under dry and wet fatigue conditions - Barry, James Nicholas; Carr, Alun J.; Dowling, Denis P. (International Conference on Plasma Surface Engineering, 2013)
Hydroxyapatite (HA) is widely used as a bio-medical coating on press-fit (cementless) orthopaedic implants to enhance the biological response of the device. Presently atmospheric plasma spray (APS) is the most widely applied technology for the deposition of such bio-medical coatings. There have been concerns however, regarding the high deposition temperatures to which the HA precursor powder is exposed during APS processing, as this can result in changes to the HA powder’s crystallinity. Furthermore, concerns have been raised regarding the affect these crystalline alterations may have on the solubility of the deposited HA coating, and thus, the affect they may have on the integrity of the coating at the metal interface. The aim of this study is to evaluate the fatigue performance of APS HA coatings, carried out under both dry and wet fatigue conditions. The wet fatigue conditions were facilitated using a Simulated Body Fluid (SBF) solution, which enabled the in vitro simulation of the HA coating response in a typical in vivo environment. SEM and XRD examination of both the reference (as received) and dry samples demonstrated the coating properties were almost identical after 10 million cycles, while the evaluation of the wet samples suggested complete failure of the HA coating had occurred during testing. In conclusion, HA coating delamination during the wet fatigue testing was attributed to significant weakening of the coating, due to material loss from dissolution as a result of exposure to the SBF solution. Significantly the dissolution was found to occur both at the interface and within the coating.